Inter-industry linkages in local economies - Frank Neffke; Martin Henning (European Regional Science Association (ERSA), 2011)
We investigate the extent to which a local industry is affected by an overrepresentation of related industries in the local economy. We focus on two types of inter-industry relatedness, namely, the degree to which two industries can employ a similarly skilled labor force and the degree to which two industries are connected in the value chain. We decompose changes in the employment of a local industry into the employment generated or destroyed in incumbent plants and the employment changes due to plant entry and exit. Furthermore, we classify new plants by the type and geographical origins of the plants' founders. We find that entrepreneurs have a stronger tendency than existing firms to set up plants in local industries that can draw on a strong local presence of labor market and value chain linked industries. The same holds for local founders compared to founders from outside the region. In the second part of the paper, we investigate the relative importance of the two relatedness types and whether the two types reinforce each other. We find that, in general, the growth of old plants and the employment generated in new plants is more strongly associated with the relatedness through the labor market. Moreover, for in new plant formation, the two relatedness types indeed tend to reinforce each other. In fact, local value chain linkages seem to be only important if client and supplier firms can also engage in labor sharing.
Keywords: 330